The Effects of Resistance and Aerobic Exercises on Adiponectin, Insulin Resistance, Lipid Profile and Body Composition in Adolescent Boys with Obesity - AGOPYAN, ANİ; ÇOTUK, HASAN BİROL; KÜÇÜK YETGİN, MERAL (ISTANBUL TRAINING & RESEARCH HOSPITAL, 2020)
Introduction: This present study aimed to examine the effects of long-term resistance exercise (REG) and aerobic exercise (AEG) on the adiponectin, insulin resistance, lipid profile and body composition in adolescent boys with obesity. Methods: Sixteen obese adolescent boys (age: 16.81 +/- 0.91 years) who studied at high school in Istanbul voluntarily participated in the study. The participants were randomly divided into two groups of (REG; n=8) and (AEG; n=8). The participants followed their exercise schedule for six months (3 days/wk, 60 min/day). The serum lipid profile, adiponectin, glucose, insulin resistance (HOMA-IR) levels and body composition of the participants were evaluated at the beginning and end of the study. A Wilcoxon matched-pairs signed-rank test and Mann-Whitney U test were used for analyses, and the criterion for statistical significance was set at p<0.05. Results: HOMA-IR, insulin, glucose and serum lipid levels decreased in both groups (p<0.05). Adiponectin and high-density lipoprotein increased only in the AEG (p<0.05). Low-density lipoprotein level was statistically decreased only in the REG (p<0.05). Conclusion: These results indicated that both types of exercises had positive effects on insulin resistance, per cent body fat, weight and fat-free body mass. Long-term (6 months) aerobic and REG had different positive effects on adiponectin and the lipid profile. Although the effects of long-term aerobic exercise on biochemical parameters are higher than REG, it was remarkable that REG proved to be an alternative model to AEG.
Keywords: Adiponectin; insulin; lipid profile; exercise; obesity; INFLAMMATORY MARKERS; PHYSICAL-ACTIVITY; OVERWEIGHT; LEPTIN; CHILDREN; FAT; METAANALYSIS; SENSITIVITY; ADIPOSITY; OUTCOMES